(untitled) (Bangladesh Heart Journal, 2023)
Background: Most countries in the world faced two waves of Corona virus disease-19 (COVID-19). But there is a lack of data regarding the wave-wise comparison of epidemiological and clinical characteristics of the COVID-19 outbreak. This study aimed to compare the demographics, clinical characteristics, and in-hospital outcomes of two waves of the COVID-19 pandemic in Bangladesh. Methods: This prospective cross-sectional study was carried out at the National Heart Foundation Hospital & Research Institute. From April 3, 2020, to January 28, 2021, was considered the first wave, and from February 27, 2021, to September 25, 2021, was considered the second wave. COVID-positive patients and all admitted patients who became COVID-19 positive during these periods were included in this study for comparison. Results: The first wave included 727 patients, and the second wave included 858 patients. The mean age of the patients in the first wave was 48.11 15.75 years, and in the second wave it was 50.65 16.63 years. Males were predominant in both waves. Healthcare personnel were less affected during the second wave (11.9% vs. 30.7%; p=0.001). Hypertension, chronic kidney disease, and cardiovascular disease were more prevalent in the second wave (p 0.05), and dyslipidemia and obesity in the first wave (p<0.05). During the second wave, 80.5% of patients were unvaccinated. Asymptomatic patients were predominant in the second wave (26.9% vs. 17.5%; p=0.001). COVID-19-related symptoms (fever, body ache, headache, anosmia, sore throat, shortness of breath, and diarrhea) were less prominent during the second wave (p<0.05). Oxygen requirements and IV antibiotic use were higher during the second wave (p<0.05). Asymptomatic & severe disease form were prevalent in second wave (p<0.05). Mortality rate was more during second wave (5.1% vs 3.4%; p=0.1). Age > 50 years, severe left ventricular dysfunction, severe and critically ill patients were the independent predictor of mortality. Conclusion: In comparison to the first wave, during the second wave symptoms were less prominent, asymptomatic and severe disease forms were more prevalent & mortality rate was high. Unvaccinated persons are more prone to affected by COVID-19. Bangladesh Heart Journal 2023; 38(1): 13-21